Edukasi Dasar Kesehatan Reproduksi dan Seksual Remaja Melalui Permainan Ular Tangga di Pondok Pesantren Minhaajurrosyidiin - Chandrayani Simanjorang; Lusyta Puri Ardhiyanti; Ika Maulida Nurrahma; Ismaya Ramadhanti; Balqis Hiri Bahasoan; Adzra Arifah Mahira; Jasmine Ayunda Saputri; Aditya Ibnu Gunawan (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: Adolescents have high curiosity that can potentially lead to risky behaviors related to reproductive and sexual health. Access to accurate information has been shown to be effective in reducing these problems. However, the implementation of reproductive health education in Islamic boarding school (pondok pesantren) settings continues to face significant barriers arising from social stigma and limited access to information, despite the fact that students (santri) remain equally vulnerable to reproductive health issues as other adolescents in the general population. This community service uses the Snakes and Ladders game as a medium to provide education to students at Minhaajurrosyidiin Islamic Boarding School as a preventive measure. Methods: The methods used in this community service are lectures and Snakes and Ladders as an interactive learning medium. Results: Knowledge was assessed through a pretest and a post-test. Baseline results showed 71.1% with poor knowledge, 28.9% with moderate knowledge, and 0% with good knowledge. Following the intervention, significant improvement occurred: good knowledge increased to 42.1%, moderate to 50%, and poor decreased to 7.9%. The mean score increased from 50.0 to 75.0, confirming that the combined lecture and Snakes and Ladders approach effectively enhanced adolescents' knowledge of reproductive and sexual health. Conclusions: Education related to reproductive and sexual health should be carried out routinely at the Minhaajurrosyidiin Islamic Boarding School, both as a form of preventing risky behavior and reproductive health problems in adolescents.